Metformin-Induced Metabolic Acidosis in Diabetic Patients attending Nakhon Phanom Hospital, 2010- 2013 - Raumcharoen, Fuangrak (Journal of Health Science of Thailand, 2017)
The objective of this study was to analyze demographic pattern, dose of metformin, clinical risk factors, severity of metformin-induced metabolic acidosis as well as the factors associated with mortality rate among patients with metformin-induced metabolic acidosis at Nakhon Phanom Hospital, Nakhon Phnom Province. Altogether 62 cases detected between 2010-2013 were reviewed. It was found that the female to male ratio of the cases was 2:1; and the most common age group were 51-60 years old (48.39%). Majority of the cases (62.50%) recieved metformin 1,000-2,000 mg/day. The risk factors identified to be associated with induced metabolic acidosis were renal insufficiency (91.93%), tissue hypoxia (75.81%), and severe infection/sepsis (41.94%). The most common complication was acute renal failure (95.16%). Most of the severe cases had pH value less than 7.1 (73.17%) and serum bicarbonate lower than 10 mEq/L (66.13%). As for the treatment outcomes, the cases with discontinuation of metformin and provision of NaHCO3 had highest mortality rate (58.62%) compared to those with only discontinuing metformin (OR = 2.59). Highest survival rate was observed among cases who discontinued metformin, obtained NaHCO3 and had hemodyalysis (83.33%). There was no association between age, dosage of metformin, severity of acidosis and the mortality rate. Significant association was observed between the treatment methods and the mortality rate (p<0.05).